Female firefighters’ increased risk of occupational exposure due to ill-fitting personal protective clothing - McQuerry, Meredith; Kwon, Cassandra; Poley-Bogan, Madeline (Frontiers in Materials, 2023)
Despite the growing female firefighter population, firefighting gear was originally designed with only the male human form in mind. As a result, women in the fire service experience issues of improper fit and injuries at rates exponentially higher than their male counterparts. Areas of ill-fit, specifically in interfaces, can increase the risk of occupational exposure for women in the fire service. The purpose of this research was to determine fit and sizing issues of personal protective clothing (PPC) to improve female firefighters’ comfort, mobility, and safety. A mixed methods approach was adopted including a nationwide questionnaire, end-user focus groups, and remote three-dimensional body scanning of 189 female structural and wildland firefighters. Between 15%–21% of female firefighters were found to intentionally leave off a part of their PPC at least “sometimes,” if not “nearly always,” with the coat and pants being the primary items not donned. 100% of participants had wrist and ankle circumferences smaller than the smallest size garment’s wrist and pant leg openings per the wildland sizing system, indicating interface areas and wildland PPC have the greatest opportunities for design and fit improvement. This study gathered and created the first and largest U.S. female firefighter anthropometric database. Overall results indicate female firefighters are wearing PPC with significant fit issues that not only reduce their comfort and restrict their mobility but pose increased safety risks related to occupational exposure.